Analysis of Knowledge, Attitude and Motivation Towards Compliance of Pandemi Covid-19 Health Protocols in Community in Banter Village, Benjeng District, Gresik Regency - Mujiono, Kukuh; Katmini, Katmini (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2021)
Coronaviruses are a large family of viruses that cause disease in humans and animals. The disease is mainly spread between people through respiratory droplets from coughs and sneezes. The design of this study is a quantitative analytic study with a cross sectional approach with the focus of the research being directed to analyze the influence of knowledge, attitudes and motivation on compliance with the Covid 19 pandemic health protocol in the community in Banter Village, Benjeng District, Gresik Regency. with a population of a number164 respondents and a sample of 116 respondents who were taken using the simple random sampling technique. Data analysis using Linear Regression test. Based on the results of the analysis multiple linear regression shows that with a p-value of 0.000 <0.05, H1 is accepted, so it can be concluded that simultaneously it exists the influence of knowledge, attitudes and motivation on compliance with the Covid 19 pandemic health protocol in the community in Banter Village, Benjeng District, Gresik Regency with a magnitude of 80.1%.It is hoped that the community can comply with health protocols as appropriate which must use standard masks, maintain distance and be diligent in washing hands with soap. That way it can reduce the risk of spreading the Covid-19 virus.